2022
DOI: 10.3390/antiox11122383
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin Alleviated CCl4-Induced Acute Liver Injury by Regulating the Nrf2 and NF-κB Signaling Pathways

Abstract: Acute liver injury has multiple causes and can result in liver failure. In this study, we evaluated the hepatoprotective ability of cyanidin (Cy) and investigated its associated mechanisms. Cy administration significantly and dose-dependently ameliorated acute liver injury induced by carbon tetrachloride (CCl4). High-dose Cy showed effects comparable to those achieved by the positive control (silymarin). Severe oxidative stress and inflammatory responses in the liver tissue induced by CCl4 were significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In addition, there was a significant decline in Th2 and Th17 cytokine gene expression in A18-treated infected mice. Considering that A18 inhibited NF-kB signaling pathway and cytokine production in infected cells in vitro, and its known immunomodulatory activity in different in vivo models [15,16], we propose that A18 may show a protective effect against pulmonary RSV infection by reducing viral infection, and by affecting the NF-κB signaling and cytokine response as well.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, there was a significant decline in Th2 and Th17 cytokine gene expression in A18-treated infected mice. Considering that A18 inhibited NF-kB signaling pathway and cytokine production in infected cells in vitro, and its known immunomodulatory activity in different in vivo models [15,16], we propose that A18 may show a protective effect against pulmonary RSV infection by reducing viral infection, and by affecting the NF-κB signaling and cytokine response as well.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding its mechanism of action, A18 was identified as an IL-17A inhibitor, resulting in the attenuation of IL-17A signaling and associated diseases in mice [14]. Importantly, A18 also inhibits the NF-κB signaling pathway and secretion of proinflammatory cytokines in different cell types and conditions in vitro and in vivo [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of molecular docking suggested that echinatin might occupy pivotal residues required for the binding of Keap1 to Nrf2, such as Gly-367, Ala-510, and Val-606. Previous studies have reported that several compounds exhibited potent anti-oxidant effects via interacting with Gly-367 and Val-606 of Keap1 [ 51 , 52 ]. Combining with the present results, we presumed that echinatin might occupy the critical binding pocket of Keap1, blocking the interaction between Keap1 and Nrf2, thereby increasing Nrf2 nuclear translocation and exerting anti-oxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a crucial transcriptional regulator of the inflammatory response, and mediators released from Kupffer cells after hepatocyte damage (such as IL-1β) activate signaling pathways, such as NF-κB in hepatic stellate cells (HSC). NF-κB activation causes HSC to activate and secrete chemokines that make HSC more sensitive to TGF, which promotes liver fibrosis ( Luedde and Schwabe, 2011 ; de Souza Basso et al, 2021 ; Ebrahim et al, 2022 ; Wang et al, 2022 ). Further evidence supports that TRAF2 is involved in collagen I transport via tyrosine kinase-interacting kinase (TNIK), and thus in the progression of liver fibrosis in mice ( Buchl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%